Electricity deregulating in UK and Turkey: A comparative assessment - (:unkn) unknown (SILA SCIENCE, 2012)
Liberation not only was adopted as the government policy by Ozal's government which came to power in 1983 but also exhibited as governance policy by Thatcher's government in UK in 1979. Both of the countries' governments intended the privatization of the foundations which are active in public sector. Privatization of the electricity sector is a natural monopoly. In addition, it was a part of long term political program of governments. In these examined processes, it is clear that UK and Turkey which is developed countries enjoyed similar restructuring targets in the early 1980s regarding electricity sector. The electricity sector gained a significant development from the early 1980s until now and day by day different solutions are found relatively in 1983-2001 and after 2001 time sequences.
Keywords: Electricity deregulating; Energy economy; Energy policy; NUCLEAR-POWER; ENERGY; BRITISH; TRANSMISSION; NETWORKS; BIOFUELS; BRITAIN; POLICY